Kedudukan Kreditur atas Objek Jaminan Fidusia yang Belum dibagi karena Adanya Perceraian - Fandi Septi Riyanto (Fakultas Hukum Universitas Islam Jember, 2019)
Fiduciary is the transfer of ownership rights of an object on the basis of trust provided thatthe object whose ownership rights are transferred remains in the possession of the owner ofthe object. Whereas what is meant by Fiduciary Guarantee is the guarantee right for movableobjects both tangible and intangible and immovable objects, especially buildings that cannotbe burdened with mortgages, which remain in the control of the Fiduciary Giver, as certaindebt repayment collateral that gives priority position to Fiduciary Recipients against othercreditors. Items loaded with a Fiduciary Guarantee must be registered. Registration for aFiduciary Guarantee is carried out at the Fiduciary Registration Office. However, if theregistration of Fiduciary Guarantee to be registered with the Office of Fiduciary Registrationis a matter of property that has not been shared with the former creditor's wife against thevehicle due to divorce, it can be said that the agreement can be canceled, so there is no legalcertainty for the recipient of Fiduciary Guarantee. If the Fiduciary Registration Office issuesand submits a Fiduciary Guarantee Certificate to the Fiduciary Recipient on the date that isthe same as the date of receipt of the application for registration. This Fiduciary GuaranteeCertificate is a copy of the Fiduciary Register Book. By obtaining a Fiduciary Guaranteecertificate, the creditor or fiduciary guarantee recipient immediately has the right of directexecution (parate execution). The legal strength of the certificate is the same as the court'sdecision which has permanent legal forceKeywords : Fiduciary Guarantee, Creditors, Execution.